Accumulation measurements from stake farm Neumayer Pegelfeld Süd, Ekström Ice Shelf, Antarctica, 2005 - Olaf Eisen; Valerie Reppert; Rolf Weller; Zsófia Jurányi (PANGAEA, 2025)
This publication series contains the accumulation measurements from stake farm Pegelfeld Süd on the Ekström Ice Shelf, Antarctica. The stake farm, located approximately 6 km to the southwest from the past and present Neumayer Station, has been in operation since December 1990. It consists of 16 aluminum poles (balise), placed in a grid of 4 x 4. Readings have been carried out in bi-weekly to monthly intervals by the overwintering staff of the air chemistry observatory (Spuso). Each data set in the series contains all measurements of each stake from one calendar year in a csv file, the average accumulation of the stake farm for each measurement and the standard deviation of the stake farm for each measurement. The data sets are accompanied by figures illustrating the development of the cumulative accumulation since the beginning of the measurements to date, a bar chart of the monthly accumulation for the year and a collection of panels (one panel per measurement) illustrating the variation of accumulation within the stake farm.
In: Eisen, O et al. (2025): Time series of accumulation measurements from stake farm Neumayer Pegelfeld Süd, Ekström Ice Shelf, Antarctica, since 1991 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.972104